Role of Dietary and Lifestyle Modifications in the Secondary Prevention of Biomarkers of Plaque recurrence in Omani Coronary Revascularized Patients - Ali, Amanat; Al-Alawi, Noura S.M.; Sadiq, Muhammad Athar; Waly, Mostafa I. (Journal of Pharmacy and Nutrition Sciences, 2020)
Objective: To assess the role of various dietary and lifestyle modifications in the secondary prevention of biomarkers of plaque recurrence in Omani coronary revascularized patients. Methods: Seventy-two patients, from the outpatient cardiology clinic of Sultan Qaboos University Hospital, were included in the study after obtaining an informed consent. In a questionnaire-based study, we collected data about four lifestyle modifications; physical activity, weight reduction, dietary intake and healthy eating patterns and smoking or non-smoking status, in personal interviews. A modified previously validated study questionnaire, which comprised of a semi-quantitative food frequency questionnaire, was used to assess the demographic information, eating patterns, diet quality index score, and daily dietary intake of study participants. The data about patient’s baseline characteristics, revascularization information and biochemical laboratory tests was harvested from the SQUH’s electronic record system. The statistical analysis of data was made using R-studio v.7 and Microsoft excel v.7. Results: The males had higher educational level as compared to females and were more active than females. The data indicated that 16% males and females were diabetic, 10% males and 21% females were hypertensive, and 30% males and 42% females had both diabetes and hypertension. Forty eight percent males and 63% females had body mass index (BMI) >30. However, no significant (P < 0.05) differences were observed in the BMI, diabetes and hypertension status in males and females. Both genders had poor nutritional knowledge. Although the LDL-C and HDL-C values in males and females differed, they were within the normal therapeutic limits. The HbA1c and C-reactive protein values were above the normal ranges with no significant (P < 0.05) difference in both males and females. The average daily energy intake in males (2694 kcalories) was significantly higher compared to females (1603 kcalories). The proportionate contribution of energy from macronutrients was within the acceptable macronutrient distribution ranges. Omani diet score for males (75.5) and females (74.6) didn’t differ significantly (P < 0.05), indicating their adherence to healthy dietary patterns. Conclusions: The results suggest that dietary and lifestyle modifications play significant role in the secondary prevention of biomarkers of plaque recurrence in Omani coronary revascularized patients. Behavioral counseling to promote healthy modifications in dietary and lifestyle factors are therefore recommended in the secondary prevention of risk of plaque recurrence.